Improvement of fucoxanthin oral efficacy via vehicles based on gum Arabic, gelatin and alginate hydrogel - Yang Li; Xiaoyu Dou; Jianhui Pang; Mengqi Liang; Chao Feng; Ming Kong; Ya Liu; Xiaojie Cheng; Ying Wang; Xiguang Chen (Journal of Functional Foods, 2019)
The improvement of the stability of fucoxanthin in gastrointestinal tract is an important approach to enhance its edible efficacy. In this study, we designed complex carriers, which were composed by gum Arabic/gelatin microcapsules and alginate hydrogel beads (GA/GE/Alg-Beads), as gastric acid resistant vehicles for oral delivery of fucoxanthin. Various parameters of the obtained fucoxanthin loaded GA/GE/Alg-Beads (FX:GA/GE/Alg-Beads) were characterized. In vitro release rate assay showed that more than 90% of the encapsulated fucoxanthin was released in simulated intestine fluid (SIF), indicated the beads could protect fucoxanthin while incubated in simulated gastric fluid (SGF). In vivo oral efficacy assay exhibited that FX:GA/GE/Alg-Beads could more effectively lower the blood lipid and oxidative stress level of experimental mice than free fucoxanthin. These results demonstrated the beads are favorable oral delivery systems for fucoxanthin and other biologically active substances which are unstable in gastric acid.